Perlindungan Hukum Anak Luar Kawin yang Mendapat Wasiat Terkait Sengketa dengan Anak Sah Menurut Hukum Perdata - Mufidatul Ahada; Felicitas Sri Marniati; Khoirul Anwar (Pusat Riset dan Inovasi Nasional, 2026)
Based on the Constitutional Court Decision Number: 46 PUU-VIII/2010, Article 43 Paragraph (1) of the Marriage Law states that a child born outside of marriage has a civil relationship with their mother and her family, as well as with the man as their father, which can be proven by science, technology, and/or other legal evidence. The child also has a blood relationship, including a civil relationship with the father's family. Inheritance for an illegitimate child through a will is allowed, but it often causes disputes as it is considered to harm the inheritance rights of legitimate children. This study aims to analyze the resolution of inheritance disputes between an illegitimate child who receives a will and a legitimate child according to civil law, as well as the legal protection of an illegitimate child in disputes with a legitimate child. The method used is normative juridical research with a literature study, using primary, secondary, and tertiary legal sources. The approaches used include the Statutory Approach, Conceptual Approach, Analytical Approach, and Case Approach. The research results show that the dispute resolution starts with a non-litigation route through deliberation, but if unsuccessful, the illegitimate child resorts to the contending method to defend their inheritance rights. The researcher recommends amendments to Article 874 of the Civil Code to grant the right to a will for an illegitimate child as long as it does not exceed the legitime portie, and to create codification related to marriage property law and wills.